Additional records of the laomediid mud-shrimp genus Naushonia Kingsley, 1897 (Crustacea: Decapoda: Gebiidea), with a revised identification key - Komai, Tomoyuki; Anker, Arthur (Zootaxa, 2015)
Six species of the peculiar mud-shrimp genus Naushonia Kingsley, 1897 (Laomediidae) from various localities in the world are treated in this study: N. carinata Dworschak, Marin & Anker, 2006 (newly recorded from Japan); N. japonica Komai, 2004 (second record since the original description); N. lactoalbida Berggren, 1992 (newly recorded from Papua New Guinea); N. portoricensis (Rathbun, 1901) (newly recorded from the French Antilles); N. serratipalma Komai & Anker, 2010 (newly recorded from Saudi Arabia); and N. draconis Anker, 2014 (newly recorded from Cuba). A detailed description and new illustrations are provided for N. portoricensis, a species for which a modern description was hitherto unavailable. Gill formula was re-examined in all six species. Colour photographs of living or fresh specimens are provided for most species. A revised key to all known species of Naushonia is presented, a eliminating misinterpretation of an important character in previous keys.